If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 10y = 15x + 6y Solving 3x + 10y = 15x + 6y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 3x + -15x + 10y = 15x + -15x + 6y Combine like terms: 3x + -15x = -12x -12x + 10y = 15x + -15x + 6y Combine like terms: 15x + -15x = 0 -12x + 10y = 0 + 6y -12x + 10y = 6y Add '-10y' to each side of the equation. -12x + 10y + -10y = 6y + -10y Combine like terms: 10y + -10y = 0 -12x + 0 = 6y + -10y -12x = 6y + -10y Combine like terms: 6y + -10y = -4y -12x = -4y Divide each side by '-12'. x = 0.3333333333y Simplifying x = 0.3333333333y
| 3(5x+1)=-12 | | 2-1x=5(x+4) | | 3t-1+t-5t=1 | | 3+-1+-5=1 | | 5x(x-2)+20=12 | | 0.33(6y-9)=-2y+13 | | 9m-10=1+6m | | 2b+5+7b-7=25 | | 3x(x+1)=2(2x+1) | | 7(k+9)=84 | | -6+3z=-9 | | 9y^2+18y+5=0 | | 9x^2-36x+40=0 | | 16m^2+9-24m=0 | | 12x^2-16x=0 | | 25+4x=5 | | 7x+1=7+5x | | x^2-6x+12=19 | | -3x-5y=6 | | .3x^2-1.7x+1=0 | | 2=x-4 | | 3n+7=34 | | 21u^2-14u=0 | | 5x+7=-10x+8 | | y=2x^2-9x+4 | | 27x=23 | | 2b-7=23 | | 3p^2-28p+49=0 | | 4x^2+3x=3x^2-4x+18 | | 12=1-x | | 98n^3+147n^2+56n+84=0 | | (2x-1)(3x+5)=5 |